Soluble vascular cell adhesion molecule 1 and N-terminal pro-B-type natriuretic peptide in predicting ischemic stroke in patients with cerebrovascular disease. - Campbell, D; Woodward, M; Chalmers, J; Colman, SA; Jenkins, A; Kemp, B; Neal, B; Patel, A; MacMahon, S (2006)
BACKGROUND: Patients with stroke or transient ischemic attack are at high risk of another stroke, and there is need for improved strategies to predict recurrent stroke. OBJECTIVE: To assess the prognostic value of levels of soluble vascular cell adhesion molecule 1 (sVCAM-1), N-terminal pro-B-type natriuretic peptide (NT-proBNP), C-reactive protein, homocysteine, renin, and lipids and lipoprotein particle concentration and size in patients with previous stroke or transient ischemic attack. DESIGN, SETTING, AND PARTICIPANTS: A nested case-control study of participants of the Perindopril Protection Against Recurrent Stroke Study was performed. The Perindopril Protection Against Recurrent Stroke Study was a placebo-controlled trial of a perindopril erbumine-based, blood pressure-lowering regimen that reduced ischemic stroke risk by 24% among individuals with previous stroke or transient ischemic attack. Each of 252 patients who experienced ischemic stroke during a mean follow-up of 3.9 years was matched to 1 to 3 control patients. Matching variables were age, sex, treatment allocated, region, and most recent qualifying event at randomization. MAIN OUTCOME MEASURES: Risk of ischemic stroke predicted by baseline levels of sVCAM-1, NT-proBNP, C-reactive protein, homocysteine, renin, and lipids and lipoprotein particle concentration and size. RESULTS: Levels of sVCAM-1 and NT-proBNP predicted recurrent ischemic stroke. The odds ratio for patients in the highest, as compared with the lowest, quarter was 2.24 (95% confidence interval, 1.35-3.73) for sVCAM-1 level and 1.62 (95% confidence interval, 0.98-2.69) for NT-proBNP level, after adjustment for matching and other risk factors. Patients in the highest quarters for both sVCAM-1 and NT-proBNP levels had 3.6 times the risk of recurrent ischemic stroke compared with patients in the lowest quarters for both biologic markers. Level of sVCAM-1 was similarly predictive of ischemic stroke in patients allocated to placebo and perindopril-based therapy. Baseline plasma levels of C-reactive protein, homocysteine, renin, and lipids and lipoprotein particle concentration and size did not predict recurrent ischemic stroke risk. CONCLUSION: Measurement of sVCAM-1 and NT-proBNP levels provides prognostic information for recurrent ischemic stroke beyond traditional risk factors.